TEORI-TEORI SOSIOLOGI DALAM PENDIDIKAN DAN APLIKASINYA BAGI PENGEMBANGAN PENDIDIKAN AGAMA ISLAM - Merisa; Sri Bulan; Yogi Azhari Nainggolan; Januar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the important role of sociological theory in education, focusing on its contribution to strengthening the function of Islamic Religious Education (PAI). Education is not only understood as a means of transferring knowledge, but also as a medium for the formation of morals and character, and a driver of social change. The purpose of this study is to provide a theoretical understanding of the relevance of sociological theories, particularly structural functionalism, symbolic interactionism, conflict theory, and exchange theory, in supporting Islamic Religious Education (PAI) learning practices. The research method used is a literature study by reviewing various relevant books and scientific articles. The analysis was conducted using a descriptive-analytical approach by connecting theoretical concepts with real phenomena in the practice of Islamic Religious Education in schools. The results show that functional theory emphasizes the role of PAI in creating social order and moral values, symbolic theory explains the meaning of religious interactions between teachers and students, conflict theory highlights the issue of unequal access to Islamic Religious Education, while exchange theory explains the reciprocal relationship that builds learning motivation. Thus, the integration of sociological theories contributes to the development of PAI that is more contextual, inclusive, and relevant to the challenges of the times.